The Role of 18F-FDG PET/CT in Guiding Precision Medicine for Invasive Bladder Carcinoma - Girard, Antoine; Vila Reyes, Helena; Shaish, Hiram; Grellier, Jean-François; Dercle, Laurent; Salaün, Pierre-Yves; Delcroix, Olivier; Rouanne, Mathieu (Frontiers in Oncology, 2020)
Bladder cancer (BC) is the tenth most common cancer worldwide. Approximately one quarter of patients with BC have muscle-invasive disease (MIBC). MIBC carries a poor prognosis and choosing the optimal treatment option is critical to improve patients’ outcomes. Ongoing research supports the role of 2-deoxy-2-(18F)fluoro-D-glucose positron emission tomography (18F-FDG PET) in guiding patient-specific management decisions throughout the course of MIBC. As an imaging modality, 18F-FDG PET is acquired simultaneously with either CT or MRI to offer a hybrid approach combining anatomical and metabolic information that complement each other. At initial staging, 18F-FDG PET/CT enhances the detection of extravesical disease, particularly in patients classified as oligometastatic by conventional imaging. 18F-FDG PET/CT has value in monitoring response to chemotherapy, as well as in localizing relapse after treatment. In the new era of immunotherapy, 18F-FDG PET/CT may also be useful to monitor treatment efficacy as well as to detect immune related adverse events. With the advent of artificial intelligence techniques such as radiomics and deep-learning, these hybrid medical images can be mined for quantitative data, providing incremental value over current standard-of-care clinical and biological data. This approach has the potential to produce a major paradigm shift towards data-driven precision medicine with the ultimate goal of personalized medicine. In this review we highlight current literature reporting the role of 18F-FDG PET in supporting personalized management decisions for patients with MIBC. Specific topics reviewed include the incremental value of 18F-FDG PET in prognostication, pre-operative planning, response assessment, prediction of recurrence, and diagnosing drug toxicity.